Chorebus (Phaenolexis) sakhalinicus TOBIAS 1998 - Papp, J. (Zenodo, 2007)
Chorebus (Phaenolexis) sakhalinicus TOBIAS, 1998 – 1 ♂: KU 22. – Described by 1 ♀ + 1 ♂ from Sakhalin. New to the fauna of Korea. – Antenna with 43 antennomeres, hind tibia and tarsus equal in length, first tergite 2.3 times length of hind breadth. Published as part of Papp, J., 2007, Braconidae (Hymenoptera) From Korea Xxii. Subfamily Alysiinae, pp. 1-38 in Acta Zoologica Academiae Scientiarum Hungaricae 53 (1) on page 9, DOI: 10.5281/zenodo.5731826